Some Curvature Properties of D-conformal Curvature Tensor on LP-Sasakian Manifolds - Shah, Riddhi Jung (Journal of Institute of Science and Technology, 2015)
This paper deals with the study of geometry of Lorentzian para-Sasakian manifolds. We investigate some properties of D-conformally flat, D-conformally semi-symmetric, Xi-D-conformally flat and Phi-D-conformally flat curvature conditions on Lorentzian para-Sasakian manifolds. Also it is proved that in each curvature condition an LP-Sasakian manifold (Mn,g)(n>3) is an eta-Einstein manifold. Journal of Institute of Science and Technology, 2014, 19(1): 30-34